Hubungan Hedonic Shopping Motivation dan Price Discount Dengan Impulse Buying Pada Konsumen Malang Town Square (Studi Pada Mahasiswa FEB Unisma Angkatan 2017) - Erika Niswatun Nur Aziza; Nurhajati Nurhajati; Muhammad Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the extent of the relationship between Hedonic Shopping Motivation and Price Discount with Impulse Buying in Malang Town Square consumers, a study on students of the faculty of Economics and Business Islamic University of Malang Class of 2017.The type of research used explanatory research. The population in this study amounted to 848 students. The sampling method in this study used purposive sampling and obtained a sample of 89 respondents.The data collection method was using google form which was distributed to students of the Faculty of Economic and Business Islamic University of Malang according to the sampling criteria. To find out the result of this study using the instrument test, normality test, classical assumption test, multiple linier regression analysis, F test, t test, and coefficient of determination test. The result shows that, Hedonic Shopping Motivation and Price Discount simultaneously have  a significant positive  effect on Impulse Buying, Hedonic Shopping Motivation has a significant positive effect on Impulse Buying, and Price Discount has a significant positive effect on Impulse Buying in Malang Town Square Costumers, a studi on students FEB Unisma Class of 2017. Keyword : Hedonic Shopping Motivation, Price Discount, Impulse Buying